Binding of a TlCl Entity by a Tetragold Tetramercaptothiacalixarene Metalloligand via Metallophilic Interactions. Issue 32 (7th May 2021) - Frank, N.; Pryjomska‐Ray, I.; Grubert, L.; Hecht, S.; Usvyat, D.; Limberg, C.
Abstract: The successive auration of p‐tert ‐butyltetramercaptotetrathiacalix[4]arene, H4 (MTC[4]), with gold(I) phosphine units was investigated. Through deprotonation with NaOMe, followed by salt metathesis reactions with (PR3 )AuCl (R=Me, Ph) complexes with two and three [(PR3 )Au] + moieties could be prepared and isolated, namely [(Ph3 PAu)2 H2 (MTC[4])] and [(Me3 PAu)3 H(MTC[4])]. In [(Me3 PAu)3 H(MTC[4])] two gold atoms already come close enough to undergo aurophilic interactions. To introduce a fourth [(PR3 )Au] + entity TlOEt had to be used for the deprotonation, which led to the finding that four gold atoms organised by the (MTC[4]) 4− coordination platform are able to bind and stabilize a TlCl entity, yielding [(Me3 PAu)4 TlCl(MTC[4])]. As evidenced by structural and theoretical investigations the binding occurs through strong metallophilic interactions, which lead to photoluminescence at low temperatures. Abstract : p‐tert ‐Butyltetramercaptotetrathiacalix[4]arene was used as a coordination platform to synthesize and investigate gold(I) complexes with varying nuclearity. Aiming at the corresponding tetranuclear complex through salt metathesis it was found capable of binding a neutral, molecular TlCl entity by metallophilic interactions, as shown by structural and theoretical investigations. These Interactions lead to photoluminescence at low temperatures (see figure).